The conception of language training of applicants for higher medical education (model 1 – the English-language mode of study) - Natalia Ushakova; Tatyana Alekseenko (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки, 2019)
The article is devoted to the conceptual development of the Ukrainian language training for foreigners who get the higher medical education in Ukraine. The tasks of Ukrainian language training of the non-native speakers who study in English have features determined by the specific communicative needs of this contingent. In order to identify such needs, the methodological approaches of the educational paradigm, which are relevant for the training of students who get higher medical education, are analyzed. At the methodological level of paradigm axiological (value), acmeological (professionally oriented), educational, strategic and problem-based approaches are outlined. Intercultural, communicative-cognitive, effective educational space approaches are distinguished at the socio-cultural level taking into account the level of proficiency in a foreign language. The task of the approaches of linguo-didactic level of the paradigm is the implementation of the above mentioned approaches in the application of methods and the creation of teaching resources, taking into account the metalinguistic, semiotic, polygraphic aspects of educational materials. The methods, the application of which in the process of language preparation ensures the realization of the communicative needs of non-native speakers, the main of which is the conscious-practical method, have been defined. To determine the communicative needs on the basis of the principle of frequency, the cataloging of communicative situations in the educational and professional sphere of communication relevant for educational migrants who receive medical education in English in the Ukrainian-speaking world is carried out. The current status of the methodological support of the educational process is described. The recommendations for optimizing the educational process organization based on the results of the study are summarized.